2021
DOI: 10.1186/s13048-021-00870-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and therapeutic insight into the effects of cinnamon in polycystic ovary syndrome: a systematic review

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common endocrine diseases in the women at their reproductive age. Nowadays, the use of herbal compounds for lesser side effects, as compared to drug treatments, has become popular for the prevention and reduction of the complications of this disease. Evidence suggests that cinnamon, given its antioxidant and anti-inflammatory properties, can be associated with reduced metabolic complications from chronic non-communicable diseases. This systematic review aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…As a result, cinnamon seems to be as effective as metformin in increasing the Insulin sensitivity. In line with this study, Maleki et al showed that HDL and insulin sensitivity were increased by the cinnamon supplementation while LDL, TG, and blood glucose were decreased in patients with PCOS ( 17 ). Supplementation with cinnamon has direct connection with lowering oxidative stress, leptin, total energy expenditure and liver enzymes, factors that may lead to an improvement in HOMA-IR ( 37 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As a result, cinnamon seems to be as effective as metformin in increasing the Insulin sensitivity. In line with this study, Maleki et al showed that HDL and insulin sensitivity were increased by the cinnamon supplementation while LDL, TG, and blood glucose were decreased in patients with PCOS ( 17 ). Supplementation with cinnamon has direct connection with lowering oxidative stress, leptin, total energy expenditure and liver enzymes, factors that may lead to an improvement in HOMA-IR ( 37 ).…”
Section: Discussionsupporting
confidence: 81%
“…The final sample was estimated including a 20% probable drop-out for each group. A minimum detectable effect size (i.e., of lab endpoints) of 0.3 was considered clinically plausible using data from previous investigations utilizing ginger and cinnamon supplementations (9,11,(16)(17)(18). Our calculated sample size was 80 participants (20 participants per group).…”
Section: Participantsmentioning
confidence: 99%
“…(iii) decrease in phosphoenolpyruvate carboxykinase (PEPCK) and the glucose-6-phosphatase activity and subsequent gluconeogenesis in the liver (Silva et al, 2022). It seems that bioactive compounds of cinnamon exert these actions by activating insulin signaling pathways (Maleki et al, 2021). The AMP-activated protein kinase (AMPK) plays a mediating role between cinnamon and insulin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, cinnamon can regulate glycemic responses by three endogenous pathways, including (i) increase in glucose transporter 4 (GLUT4) production and translocation and subsequent glucose uptake in muscle and adipose tissue, (ii) decrease in glycogen synthase kinase 3 (GSK3) activity and subsequent promotion of glycogen synthase activity, and (iii) decrease in phosphoenolpyruvate carboxykinase (PEPCK) and the glucose‐6‐phosphatase activity and subsequent gluconeogenesis in the liver (Silva et al, 2022). It seems that bioactive compounds of cinnamon exert these actions by activating insulin signaling pathways (Maleki et al, 2021). The AMP‐activated protein kinase (AMPK) plays a mediating role between cinnamon and insulin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that cinnamon has the capacity to improve glucose control in humans [ 99 ]. Indeed, a study examined the effects of cinnamon in people living with diabetes at three different doses: 1, 3, and 6 g/day for 40 days, finding it decreased FBG levels significantly [ 72 ].…”
Section: Herbal Approaches To Management In Metabolic Syndromementioning
confidence: 99%